2018
DOI: 10.1002/jcp.27075
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer properties of tocotrienols: A review of cellular mechanisms and molecular targets

Abstract: Vitamin E is composed of two groups of compounds: α-, β-, γ-, and δ-tocopherols (TPs), and the corresponding unsaturated tocotrienols (TTs). TTs are found in natural sources such as red palm oil, annatto seeds, and rice bran. In the last decades, TTs (specifically, γ-TT and δ-TT) have gained interest due to their health benefits in chronic diseases, based on their antioxidant, neuroprotective, cholesterol-lowering, anti-inflammatory activities. Several in vitro and in vivo studies pointed out that TTs also exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 202 publications
(318 reference statements)
1
28
0
Order By: Relevance
“…Although many studies in the literature have reported the anti-tumor effect of T3 in vitro and in vivo [29,59], very few studies have focused on the potency of beta-tocotrienol in this respect. Beta-T3 is known for its low abundance in nature, which makes its extraction difficult; however, it is found to be the predominant vitamin E form in all 6 tested varieties of whole wheat with amounts ranging from 0.9 to 1.9 mg /100 mg of wheat [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many studies in the literature have reported the anti-tumor effect of T3 in vitro and in vivo [29,59], very few studies have focused on the potency of beta-tocotrienol in this respect. Beta-T3 is known for its low abundance in nature, which makes its extraction difficult; however, it is found to be the predominant vitamin E form in all 6 tested varieties of whole wheat with amounts ranging from 0.9 to 1.9 mg /100 mg of wheat [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, literature is focusing on the importance of tocotrienols especially with several data showing superiority of tocotrienols as antioxidants compared to tocopherols [19,20], in addition to their role as anti-inflammatory [21,22], hypoglycemic [23], immuno-stimulatory [1], cardio- [24,25], hepato- [26], neuro- [27] and nephro-protective agents [28]. Moreover, many anti-cancer effects of tocotrienols have been documented in vitro and in vivo involving proliferation, metastasis, apoptosis and angiogenesis pathways [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies (published in 2011‐2019) are summarized in Table 4. Earlier work has been covered by some excellent recent reviews 7–9,12 and a book 115 . Some of the proposed molecular targets or pathways are highlighted in Figure 3.…”
Section: Laboratory Studies On Ve and Cancer Preventionmentioning
confidence: 99%
“…In 2010, we reviewed the cancer‐preventive activities of tocopherols and tocotrienols 2 . Since then, this topic has been studied by a large number of investigators and reviewed by different authors 7–12 …”
Section: Introductionmentioning
confidence: 99%